Pengaruh Kompetensi Terhadap Kinerja Pegawai Dengan Motivasi Sebagai Variabel Moderating di Rektorat Universitas Palangka Raya - Rusdiana Rusdiana; Meitiana Meitiana; Achmad Syamsudin (Edunomics Journal, 2023)
This study aims to analyze the effect of competence on employee performance with motivation as a moderating variable. The method used in this research is explanatory research. The sample of this research is 63 people. Data were analyzed using descriptive analysis and inferential statistical analysis using the Structural Equation Modeling (SEM) model using the Partial Least Squares (SEM-PLS) approach. The results of the study concluded that COMPETENCY directly affects employee performance. In this connection, motivation is not a moderating variable. The implications of this study illustrate that motivation has not been effective in developing HR strategies within the Rectorate of Palangka Raya University. Therefore, leaders, in order to improve motivation.